PENGARUH TAX PLANNING TERHADAP NILAI PERUSAHAAN - Nanik Lestari (Department of Accounting-Faculty of Economic and Business (FEB), 2014)
The purpose of this research is to analyze the impact of tax planning on firm.Tax planning is the first step in tax management which at this stage of collection and researchon tax laws, with a view can be selected kinds of austerity measures taxes that will be done.The research was conducted for non banking and financial firms in Indonesia Stock Exchangefrom 2010 to 2011. The results of this study are: Firstly, we found evidence of positiverelationship between tax planning and firm value. With improvements in the company in taxplanning activities will further enhance the company's value. Finally, the results of thesensitivity test with the main model and the full sample suggested that tax planning had arobust positive effect in increasing firm valueDOI: 10.15408/akt.v7i1.2647